The Influence of Marketing Research on the Profitability of Nigerian Deposit Money Banks in Abuja, Nigeria - Marcus Garvey Orji (Britain International for Academic Research (BIAR-Publisher), 2022)
The objective of this study was to examine the influence of marketing research on the profitability of Nigerian Deposit Money Banks in Abuja. The study was a survey research sampling the opinion of 82 staff of Zenith, Polaris, First Bank and First city monument bank, Bwari branch. Their opinion was collected using a structured questionnaire. The data obtained was analysed by tabulation and percentages, and the formulated hypotheses tested using Kendal coefficient of concordance method. The findings revealed that Banks marketing research efforts results to customer’s need identification and customer’s satisfaction; and that bank’s customer’s satisfaction through marketing research efforts enhances profitability in Abuja. The study concluded that for Deposit Money banks to maximize profit at optimum level, they have to expand the scope of marketing research and development in order to eliminate the risk involve in today’s marketing trend. Therefore the study recommended among other things that Deposit Money Banks in Nigeria should strive to monitor the degree of customer’s satisfaction with their services on a continuous basis through market situation analysis. This way, the banks will be able to see areas requiring improvement thereby facilitating the much-desired satisfactory delivery of financial services to Abuja residents. Also Banks should intensify their research efforts to provide timely information on product development and other areas that will have positive influence on their operations. Equally they should ensure that all their marketing research efforts are tailored towards customer needs and to identify not just the explicit needs of the customer, but also the latent needs.